The SnRK1 Energy Sensor in Plant Biotic Interactions. (August 2016) - Hulsmans, Sander; Rodriguez, Marianela; De Coninck, Barbara; Rolland, Filip
Abstract : Our understanding of plant biotic interactions has grown significantly in recent years with the identification of the mechanisms involved in innate immunity, hormone signaling, and secondary metabolism. The impact of such interactions on primary metabolism and the role of metabolic signals in the response of the plants, however, remain far less explored. The SnRK1 (SNF1-related kinase 1) kinases act as metabolic sensors, integrating very diverse stress conditions, and are key in maintaining energy homeostasis for growth and survival. Consistently, an important role is emerging for these kinases as regulators of biotic stress responses triggered by viral, bacterial, fungal, and oomycete infections as well as by herbivory. While this identifies SnRK1 as a promising target for directed modification or selection for more quantitative and sustainable resistance, its central function also increases the chances of unwanted side effects on growth and fitness, stressing the need for identification and in-depth characterization of the mechanisms and target processes involved. Video Abstract: Trends: Plant biotic interactions are regulated by physical barriers, innate immune responses, hormone signaling, and a plethora of secondary metabolites. It is now also becoming clear that primary (carbon and energy) metabolism is an important target as well as a source of regulatory signals affecting these interactions. The SnRK1 kinases are important metabolic sensors, integrating diverse stress conditions and maintaining energy homeostasis. An increasing number of studies suggest a key role for SnRK1-mediated signaling in plant interactions with viral, bacterial, fungal, and oomycete pathogens as well as with herbivores. The exact mechanisms involved in SnRK1 regulation of plant biotic interactions are likely very diverse and, in addition to the direct targeting of pathogenicity factors, might include regulation of primary and secondary metabolism, growth and development, hormone signaling, and cell death. SnRK1 and/or its downstream processes are putative prime targets for modification and selection for a more quantitative and sustainable biotic stress tolerance.